Tropism and innate host responses of influenza A/H5N6 virus: an analysis of ex vivo and in vitro cultures of the human respiratory tract - Hui, Kenrie P. Y.; Chan, Louisa L. Y.; Kuok, Denise I. T.; Mok, Chris K. P.; Yang, Zi-feng; Li, Run-feng; Luk, Geraldine S. M.; Lee, Elaine F.; Lai, Jimmy C. C.; Yen, Hui-ling; Zhu, Huachen; Guan, Yi; et al. (The European respiratory journal, 2017)
Since their first isolation in 2013, influenza A/H5N6 viruses have spread amongst poultry across multiple provinces in China and to Laos, Vietnam and Myanmar. So far, there have been 14 human H5N6 infections with 10 fatalities. We investigated the tropism, replication competence and cytokine induction of one human and two avian H5N6 isolates in ex vivo and in vitro cultures derived from the human respiratory tract. Virus tropism and replication were studied in ex vivo cultures of human nasopharynx, bronchus and lung. Induction of cytokines and chemokines was measured in vitro in virus-infected primary human alveolar epithelial cells. Human H5N6 virus replicated more efficiently than highly pathogenic avian influenza (HPAI) H5N1 virus and as efficiently as H1N1pdm in ex vivo human bronchus and lung and was also able to replicate in ex vivo cultures of human nasopharynx. Avian H5N6 viruses replicated less efficiently than H1N1pdm in human bronchial tissues and to similar titres as HPAI H5N1 in the lung. While the human H5N6 virus had affinity for avian-like receptors, the two avian isolates had binding affinity for both avian- and human-like receptors. All three H5N6 viruses were less potent inducers of pro-inflammatory cytokines compared with H5N1 virus. Human H5N6 virus appears better adapted to infect the human airways than H5N1 virus and may pose a significant public health threat.